PENINGKATAN SKILLS PASSING BAWAH BOLA VOLI MELALUI METODE RECIPROCAL TEACHING PADA PESERTA DIDIK KELAS X TAV-1 SMK NEGERI 2 GARUT TAHUN PELAJARAN 2021/2022 - ICA SANTANA (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2022)
Physical education is a vehicle for education, which provides opportunities for children to learn important things. Therefore, Physical Education Lessons are no less important than other lessons. The purpose of this research is to find out whether the Reciprocal Teaching method can improve the skills of volleyball underpassing techniques in class X students. Audio Video Techniques 2 SMKN 2 Garut in the 2019/2020 academic year? Data collection techniques are obtained through observations made by teachers and students where in making observations there are predetermined signs, to avoid things that are subjectivity from observation or observe. The stages of this research consist of four stages, namely Plan, Action, Observation and Reflection. The subjects in this study were students of class X. TAV-1 SMK Negeri 2 Garut, totaling 36 students. Based on the results of the study, it is known that the results of the initial data to the third cycle have an increase of 292 times and an average of 8.11. Active students in cycle III amounted to 27 students or about 75%, when viewed from the initial data there was an increase of 22 students or 61.11%. The results of this study can be concluded that